Phosphorus status on Canadian organic farms - Martin, Ralph C; Lynch, Derek H; Frick, Brenda; van Straaten, Peter (Journal of the science of food and agriculture, 2007)
In eastern North America, many conventional livestock farms, especially dairy farms with high inputs of feed and fertiliser have excess soil phosphorus levels and an annual phosphorus surplus. However, a Canadian dairy farm in transition to organic, without fertiliser inputs reduced its farm P surplus to a marginal level. On long‐term organic dairy farms in Ontario, most soils tested low to very low in available P as measured by a standard soil test. Canadian Prairie organic grain farms also consistently demonstrate deficiencies in available soil P. Organic producers have few viable alternatives for P management. Phosphate rock can be acceptable to organic standards (provided they are low in heavy metals, and not processed synthetically), but the P in these becomes available slowly, especially in high pH soils common on most organic farms in Canada. An alternative is to increase soil P availability. Enhanced microbial activity in organically managed soils may make P more available. Livestock manures are rich sources of available phosphorus, but a majority of organic farmers in Canada do not keep livestock. Off‐farm manure sources are subject to organic regulations and hauling costs, both of which may be prohibitive. Furthermore, manure from conventional farms in Canada may be contaminated by genetically modified material from corn and soybean feed. Additional research is required to improve short‐term availability of soil P and long‐term replacement. Copyright © 2007 Society of Chemical Industry